2019
DOI: 10.5435/jaaosglobal-d-19-00163
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Opioid Prescription Protocol Reduces Opioid Consumption After Total Joint Arthroplasty

Abstract: Introduction: Previous studies demonstrate routine overprescription of pain medications after total joint arthroplasty (TJA). A standardized reduced opioid prescription protocol for TJA was initiated at our institution, which we hypothesized would lead to a reduction in opioid consumption compared with patients who had surgery before initiation of the new protocol. Methods: We evaluated 97 consecutive opioid-naive patients undergoing primary total knee arthroplasty (TKA) and total hip arthroplasty (THA) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…20 In another study, patients who underwent TKA in an IP setting were prescribed 115 opioid pills and consumed 76 of those, and patients who underwent THA in that setting were given 94 pills and consumed 41 of those. 21 The findings of this study agree with the findings of both of these previous studies in that TKA has higher amounts of opioids prescribed and consumed when compared with THA, but the amounts of opioids prescribed and consumed in this study across both procedures is lower in comparison. This could be due to the internal implementation and process improvements throughout our institution.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…20 In another study, patients who underwent TKA in an IP setting were prescribed 115 opioid pills and consumed 76 of those, and patients who underwent THA in that setting were given 94 pills and consumed 41 of those. 21 The findings of this study agree with the findings of both of these previous studies in that TKA has higher amounts of opioids prescribed and consumed when compared with THA, but the amounts of opioids prescribed and consumed in this study across both procedures is lower in comparison. This could be due to the internal implementation and process improvements throughout our institution.…”
Section: Discussionsupporting
confidence: 90%
“…18 With the United States being in the midst of an opioid epidemic, 19 it is important to understand the full implications surrounding opioids in TKA and THA. Numerous studies have looked at prescribing and consumption of opioids for TKA and THA in the IP settings 20-22 ; however, to the knowledge of the current authors, there have not been studies comparing opioid prescription and consumption for TKA and THA specifically in the OP setting or studies comparing the OP ASC to the IP setting.…”
Section: Introductionmentioning
confidence: 99%
“…while another study found that for every 1 pill prescribed, patients were likely to consume an additional~0.5 pill after total joint arthroplasty [17,18]. Further, standardized opioid prescription protocols have been previously shown to facilitate reduced opioid use [19]. Together, these data suggest that a standardized multimodal pain management regimen is important for improving patient outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…Previous literature suggests that strategies that limit postoperative opioid prescribing reduce the quantity of pills and oral MED prescribed by 36% and 41%, respectively. 6,18 We estimated 80 patients would be needed to detect a 40% difference in cumulative MED prescribed at discharge with a two-sided α level of .05 and power of 80%. At 80 patients, our study would also be powered to detect a 2-point absolute difference between postoperative pain scores among the two cohorts, the minimal clinically important difference.…”
Section: Discussionmentioning
confidence: 99%
“…Several guidelines provide evidence-based recommendations on opioid prescribing to limit postoperative opioid exposure, optimize multimodal analgesia, and reduce potential harm from chronic opioid exposure. 2,[6][7][8] States have implemented laws limiting the number of opioids prescribed upon discharge from acute care settings, mandating prescription monitoring program (PMP) use, and alerting providers to patients who may be seeing multiple doctors for opioid prescriptions. 9 Payers have adopted strict coverage limits for opioid-naïve patients and high-risk prescribing (eg, co-prescribing benzodiazepines at high doses above a morphine equivalent dose [MED] of 90).…”
Section: Introductionmentioning
confidence: 99%